Relationships between neuropsychological and antisaccade measures in multiple sclerosis patients - Ferreira, Marisa Borges; Pereira, Paulo Alexandre; Parreira, Marta; Sousa, Ines; Figueiredo, José; Cerqueira, João José; Macedo, Antonio Filipe (PeerJ, 2018)
Background The Stroop test is frequently used to assess deficits in inhibitory control in people with multiple sclerosis (MS). This test has limitations and antisaccade eye movements, that also measure inhibitory control, may be an alternative to Stroop. Objectives The aim of this study was twofold: (i) to investigate if the performance in the antisaccade task is altered in patients with MS and (ii) to investigate the correlation between performances in neuropsychological tests, the Stroop test and the antisaccade task. Methods We measured antisaccades (AS) parameters with an infrared eye tracker (SMIRED 250 Hz) using a standard AS paradigm. A total of 38 subjects diagnosed with MS and 38 age and gender matched controls participated in this study. Neuropsychological measures were obtained from the MS group. Results Patients with MS have higher error rates and prolonged latency than controls in the antisaccade task. There was a consistent association between the Stroop performance and AS latency. Stroop performance but not AS latency was associated with other neuropsychological measures in which the MS group showed deficits. Conclusions Our findings suggest that AS may be a selective and independent measure to investigate inhibitory control in patients with MS. More studies are necessary to confirm our results and to describe brain correlates associated with impaired performance in the antisaccade task in people diagnosed with MS.
Keywords: Eye movements; Antisaccades; Multiple sclerosis; Stroop test; Inhibitory control; Executive functions